Spatial coordinate systems for tactile spatial attention depend on developmental vision: evidence from event-related potentials in sighted and congenitally blind adult humans. - Röder, B; Föcker, J; Hötting, K; Spence, C (2008)
Changes in limb posture (such as crossing the hands) can impair people's performance in tasks such as those involving temporal order judgements, when one tactile stimulus is presented to either hand. This crossed hands deficit has been attributed to a conflict between externally and anatomically anchored reference systems when people localize tactile stimuli. Interestingly, however, the performance of congenitally blind adults does not seem to be affected by crossing the hands, suggesting a default use of an anatomically rather than an externally anchored reference system for tactile localization. In the present study, 12 congenitally blind and 12 sighted adults were instructed to attend to either the left or the right hand on a trial-by-trial basis in order to detect rare deviants (consisting of a double touch) at that hand, while ignoring both deviants at the other hand and frequent standard stimuli (consisting of a single touch) presented to either hand. Only the sighted participants performed less accurately when they crossed their hands. Concurrent electroencephalogram recordings revealed an early contralateral attention positivity, followed by an attention negativity in the sighted group when they adopted the uncrossed hands posture. For the crossed hand posture, only the attention negativity was observed with reduced amplitude in the sighted group. By contrast, the congenitally blind group displayed an event-related potential attention negativity that did not vary when the posture of their hands was changed. These results demonstrate that the default use of an external frame of reference for tactile localization seems to depend on developmental vision.